2020
DOI: 10.3390/cells9102196
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Encoded Amyloid Beta peptides—A Novel Putative Player in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is an age-related detrimental dementia. Amyloid beta peptides (Aβ) play a crucial role in the pathology of AD. In familial AD, Aβ are generated from the full-length amyloid beta precursor protein (APP) via dysregulated proteolytic processing; however, in the case of sporadic AD, the mechanism of Aβ biogenesis remains elusive. circRNAs are a class of transcripts preferentially expressed in brain. We identified a circRNA harboring the Aβ-coding region of the APP gene termed circAβ-a. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 90 publications
2
47
0
Order By: Relevance
“…circRNAs can regulated protein expression and function by interacting with the protein or through protein complex (72). Another described function of circRNAs is the ability to translate into proteins as some of them have internal ribosomal entry site (IRES) within their sequences (32). circRNAs may also act as miRNAs sponges disrupting its function as inhibitors of mRNAs (28,73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…circRNAs can regulated protein expression and function by interacting with the protein or through protein complex (72). Another described function of circRNAs is the ability to translate into proteins as some of them have internal ribosomal entry site (IRES) within their sequences (32). circRNAs may also act as miRNAs sponges disrupting its function as inhibitors of mRNAs (28,73).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APP and MAPT are genes encoding the main proteins involved in AD, i.e. amyloid precursor protein and tau protein, which circRNAs are also transcribed from (31,32). Most interestingly, A peptides may be synthesized from an APP-derived circRNA, known as circA-a (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of circRNA as a biomarker for AD has been previously demonstrated in small-scale clinical studies. For example, Mo et al ( 2020 ) suggested that circAβ-A (hsa_circ_0007556) was a promising therapeutic target in both cultured cells and brains of AD patients. Compared with traditional biomarkers for AD, circRNA has the following advantages: (i) circRNA is highly expressed in the brain—higher than in other tissues and organs—and is tissue-specific (Rybak-Wolf et al, 2015 ); (ii) the circular structure of circRNA is more stable than that of linear RNA and is resistant to enzyme digestion (Verduci et al, 2019 ); and (iii) circRNAs are transferred as exosomes from the brain to bodily fluids, thus making it easier to detect them and avoiding interference from various enzymes and humoral factors (Greene et al, 2017 ).…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…Furthermore, by performing in vivo and in vitro translation assays, circRNAs have been shown to enable cap-independent translation and generate functional proteins. Of these proteins, some have been demonstrated to play vital roles under a number of pathophysiological conditions, such as muscle-enriched circRNA circ-ZNF609 [ 10 ] and brain-ubiquitously expressed circRNA circAβ-a [ 15 ]. In addition, several mechanisms for circRNA translation have been proposed.…”
Section: Introductionmentioning
confidence: 99%